A laboratory study of fluoride concentration in infant formulas marketed in Malaysia and estimation of daily intake - Mohd Desa S.N.F.; Muhamad N.A.; Mohd Nor N.A.; Abdul Razak F.; Abdul Manan N.S.; Ab-Murat N.; Marhazlina J. (Universiti Putra Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA/MYCITE